A multicomponent intervention to increase peer-directed communication in Head Start children. - Stanton-Chapman TL; Kaiser AP; Vijay P; Chapman C (Journal of Early Intervention, 2008)
The effects of a multicomponent intervention strategy to increase peer-directed social communication in eight Head Start children at risk for poor language and social skill development were examined. The intervention consisted of three components: (a) a planning period, including reading a storybook that illustrated the play theme and use of the social pragmatic communication strategies, practice using vocabulary to be used in play, and choosing roles for the thematic activity; (b) a 10-min play session in which the interventionist coached children to interact while they played with the thematic related toys; and (c) a brief reporting period in which children reviewed their use of the social pragmatic strategies and specific vocabulary. A multiple-baseline design across dyads with pre- and postgeneralization probes was employed. Children increased their use of peer-directed communication over baseline levels, target vocabulary words, and other social pragmatic skills.